2017
DOI: 10.7150/jca.19897
|View full text |Cite
|
Sign up to set email alerts
|

ERCC1_202 Is A Prognostic Biomarker in Advanced Stage Non-Small Cell Lung Cancer Patients Treated with Platinum-Based Chemotherapy

Abstract: Purpose: To develop a qPCR method to examine the 202 isoform of excision repair cross-complementation group 1 (ERCC1_202) and to evaluate its clinical utility as a predictive biomarker for platinum-based chemotherapy in non-small cell lung cancer (NSCLC).Methods: The relative complementary DNA (cDNA) quantification for ERCC1_202 was conducted using a fluorescence-based, real-time detection method and β-actin was used as a reference gene.Results: A strong correlation was observed between ERCC1_202 mRNA and ERCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The majority of studied biomarkers for efficacy of platinum doublets are not immune biomarkers but tumor biomarkers, studied at a genomic ( 71 ), transcriptomic ( 72 ), or protein level ( 73 ) ( Figure 2 ). However, a few studies have raised the question of TILs in the context of chemotherapy.…”
Section: Baseline Predictors Of Responsementioning
confidence: 99%
“…The majority of studied biomarkers for efficacy of platinum doublets are not immune biomarkers but tumor biomarkers, studied at a genomic ( 71 ), transcriptomic ( 72 ), or protein level ( 73 ) ( Figure 2 ). However, a few studies have raised the question of TILs in the context of chemotherapy.…”
Section: Baseline Predictors Of Responsementioning
confidence: 99%
“…ACTB is widely used as a reference gene in qPCR analysis [2325]. However, in this study, the expression of ACTB was significantly down-regulated with a 0.63-fold change in Hcy-treated HUVECs (Fig 2B).…”
Section: Resultsmentioning
confidence: 61%
“…These authors found that only one-the ERCC1 isoform 202-out of four ERCC1 isoforms had a full functional capacity in NER and could be associated with cisplatin resistance in NSCLC [31]. This was confirmed by Wang et al, who showed that ERCC1 could be a prognostic marker in advanced NSCLC treated with platinum-based drugs [36].…”
Section: Nucleotide Excision Repairmentioning
confidence: 81%